Sustaining soil productivity in intensive African agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In Africa, the agricultural sector is faced with many problems. Among them is the restricted access to good agricultural land in regions where land area per capita is continually decreasing as a result of the increasing population growth. Yet it is...